Self-assembled nanodisks in coaxial GaAs/GaAsBi/GaAs core–multishell nanowires. Issue 40 (12th October 2020) - Zhang, Bin; Jansson, Mattias; Shimizu, Yumiko; Chen, Weimin M.; Ishikawa, Fumitaro; Buyanova, Irina A.
Abstract : The formation of self-assembled nanodisks open up new avenue for designing novel quantum structures by utilizing a dilute bismide. Abstract : III–V semiconductor nanowires (NWs), such as those based on GaAs, are attractive for advanced optoelectronic and nanophotonic applications. The addition of Bi into GaAs offers a new avenue to enhance the near-infrared device performance and to add new functionalities, by utilizing the remarkable valence band structure and the giant bowing in the bandgap energy. Here, we report that alloying with Bi also induces the formation of optically-active self-assembled nanodisks caused by Bi segregation. They are located in the vicinity to the 〈112〉 corners of the GaAsBi shell and are restricted to twin planes. Furthermore, the Bi composition in the disks is found to correlate with their lateral thickness. The higher Bi composition in the disks with respect to the surrounding matrix provides a strong confinement for excitons along the NW axis, giving rise to narrow emission lines (<450 μeV) with the predominant emission polarization orthogonal to the NW axis. Our findings, therefore, open a new possibility to fabricate self-assembled quantum structures by combining advantages of dilute bismide alloys and lattice engineering in nanowires.